When the mafia enters the stadium: sport and organized crime in Rome (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The aim of this article is to analyze the role of sport within the organized crime’s system active in Rome. Starting from amateur football teams of the periphery to the A national championship, Roman mafias have invested in football sector not only for laundering illicit profits, but also for reinforcing their embedment in the territory and for increasing their criminal opportunities.
Keywords: Sport, organized crime, ultras, football, local mafias